Application of Activated Carbon and Polypyrrole Coated Sawdust for Adsorption of Acidic Dye from Aqueous Solutions: A Comparative Study - Geetha, A.; Palanisamy, P.N. (Asian Journal of Chemistry, 2015)
Decolorization of textile effluents using the conventional technologies is not effective because of their limitations. A search is required for more effective and economic treatment techniques. Hence the potentiality of activated carbon (CSAC) and polypyrrole coated sawdust (PPy/SD) derived from the fruit of the gardening plant material of Cordia sebestena to remove acid orange 7 from aqueous solutions via adsorption was investigated. The batch mode adsorption studies were carried out by varying experimental parameters such as pH, initial dye concentration, contact time and temperature. The kinetic data at different concentrations at different temperatures were analyzed for both the adsorbents using pseudo first order and pseudo second order models. The equilibrium data were also analyzed by Freundlich and Langmuir models. Thermodynamic studies were also evaluated. Finally, the performance of CSAC was compared with PPy/SD. The experimental results indicated that polypyrrole coated sawdust (PPy/SD) is most suitable for the removal of acid orange 7 from aqueous solutions than activated carbon (CSAC).